Impact of Employee Welfare Facilities on Employees’ Efficiency in Nepalese Commercial Banks - Shrestha, Sarish (Nepalese Journal of Management, 2024)
This study examines the impact of employee welfare facilities on employees’ efficiency in Nepalese commercial banks. Employee efficiency is the dependent variable. The selected independent variables are work life balance, health and wellness programs, training and development opportunities, financial benefits, and career development opportunities. The primary source of data is used to assess the opinions of respondents regarding work life balance, health and wellness programs, training and development opportunities, financial benefits, and career development opportunities. The study is based on 131 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of employee welfare facilities on employees’ efficiency in Nepalese commercial banks.The study showed a positive impact of work life balance on employees’ efficiency. It indicates that better work life balance leads to increase in employee efficiency. Similarly, health and wellness programs is positively correlated to employees’ efficiency. It indicates that health and wellness leads to increase in employee efficiency. Likewise, training and development opportunities is positively correlated to employees’ efficiency. It indicates that training and development opportunities lead to increase in employee efficiency. Further, f inancial benefits are positively correlated to employees’ efficiency. It indicates that higher the financial benefits, higher would be the employees’ efficiency. In addition, career development opportunities are positively correlated to employees’ efficiency. It indicates that career development opportunities lead to increase in employee efficiency.